ANALYZING THE EFFECT OF BRAND PERSONALITY AND BRAND EXPERIENCE ON CUSTOMER LOYALTY (A STUDY OF SAMSUNG GALAXY SMARTPHONE) - Tamalero, Feiby; Tumiwa, Johan R. (FEB Universitas Sam Ratulangi Manado, 2016)
Abstract : Marketing in its course of development is in a phase in which the organizations are no more only thinking of finding new customers, and nowadays one of the most important goals of marketing is demand management through pushing customers up the loyalty ladder. Customer loyalty is considered to be among the most important and key factors for business success. The goal of the company is to create sustainability and profitability relations with their customers through offered their superior brandto achieve the competitive advantage. This research aims to analyze the brand personality and brand experience of Samsung Galaxy Smartphone on customer loyalty which is concern on 80 respondents who are the consumers. The type of analysis is using Multiple Regression Analysis. The result shows that brand personality and brand experience influence customer loyalty simultaneously. The most significant effects oncustomer loyalty are brand experience. Keywords: Brand Personality, Brand Experience, Customer Loyalty